2016
DOI: 10.2147/ijn.s111930
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable mixed MPEG-SS-2SA/TPGS micelles for triggered intracellular release of paclitaxel and reversing multidrug resistance

Abstract: In this study, a type of multifunctional mixed micelles were prepared by a novel biodegradable amphiphilic polymer (MPEG-SS-2SA) and a multidrug resistance (MDR) reversal agent ( d -α-tocopheryl polyethylene glycol succinate, TPGS). The mixed micelles could achieve rapid intracellular drug release and reversal of MDR. First, the amphiphilic polymer, MPEG-SS-2SA, was synthesized through disulfide bonds between poly (ethylene glycol) monomethyl ether (MPEG) and stearic acid (SA). The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Mitochondrial respiratory complex Ⅱ, also called succinate dehydrogenase, plays an important role in mitochondrial electron transport, which is an essential part in the tricarboxylic acid cycle as well as the mitochondrial respiratory chain 35 . TPGS can bind with mitochondrial respiratory complex Ⅱ and induce subsequent mitochondrial dysfunction, resulting in significant depletion of intracellular energy 20 , 36 . TPGS can accumulate in mitochondria and inhibit the activity of complex Ⅱ, and consequently disrupt the electron transfer and activate calcium channel, which would result in the overload of calcium and ensuing dysfunction of mitochondria.…”
Section: Tpgs Properties In Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial respiratory complex Ⅱ, also called succinate dehydrogenase, plays an important role in mitochondrial electron transport, which is an essential part in the tricarboxylic acid cycle as well as the mitochondrial respiratory chain 35 . TPGS can bind with mitochondrial respiratory complex Ⅱ and induce subsequent mitochondrial dysfunction, resulting in significant depletion of intracellular energy 20 , 36 . TPGS can accumulate in mitochondria and inhibit the activity of complex Ⅱ, and consequently disrupt the electron transfer and activate calcium channel, which would result in the overload of calcium and ensuing dysfunction of mitochondria.…”
Section: Tpgs Properties In Drug Delivery Systemsmentioning
confidence: 99%
“…The micelles exhibited 6-fold decrease of IC 50 in MCF-7/ADR cells and more efficient tumor inhibition in MCF-7/ADR bearing nude mice compared with free DOX. Moreover, Dong et al 36 designed PTX loaded mixed micelles, which were prepared with disulfide bond-linked MPEG and stearic acid (MPEG-SS-2SA), and TPGS. PTX can be rapidly released within 24 h under the reductive environment.…”
Section: Unmodified Tpgs Based Formulationsmentioning
confidence: 99%
“…TPGS was employed as the other ROS inducer in this system, which was a derivative of vitamin E and composed of polyethylene glycol and α-tocopheryl succinate (α-TOS) 24. α-TOS is the major function group of TPGS, which increases the intracellular ROS level through interfering with the function of the mitochondrial electron transport chain, thereby inducing apoptosis 25,26. Youk et al, found that TPGS generated more ROS to induce apoptosis, and effectively inhibited the growth of human lung carcinoma cells implanted in nude mice compared with TOS 27.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 0.5 ml culture medium and 0.5 ml JC-1 staining solution were added and incubated at 37 C for 20 min. Carbonyl cyanide 3-chlorophenylhydrazone (CCCP) was used as the control of MMP decrease (Dong et al, 2016). The cells were rinsed with binding buffer twice and observed under an inverted fluorescence microscope (IX73; Olympus TM , Shinjuku City, Tokyo, Japan).…”
Section: Detection Of Mitochondrial Membrane Potentialmentioning
confidence: 99%